The extension teacher in the Division of Tarlac a descriptive profile - Dacayanan, Emiliano F. 1928- ([Quezon City s.n.], 1969)
This is a descriptive profile of extension teachers in the Division of Tarlac made due to the absence of meaningful information about this particular sector of the personnel of the Department of Education.
Thesis (M.Ed.)--University of the Philippines
Keywords: Extension teachers; Teachers -- Tarlac